Reka Bentuk sistem pusat sumber digital FTSM - Rosilah Hassan,; Juhana Salim,; Syahanim Mohd Salleh,; Zarina Shukur,; Masri Ayob,; Abdullah Mohd Zin,; Mohd Shahizan Othman, (Penerbit UKM, 2004)
A resource center for a small organization such as a school or a faculty in a university do not have the budget to hire a full time librarian or to provide a highly sophisticated computerized information system. This paper discusses a system to help in managing documents in a resource center for small organizations such as Faculty of Information Science and Technology (FTSM) Universiti Kebangsaan Malaysia. The system, which is called FTSM Digital Resource Center System, is able to classify documents automatically, as well as providing normal functions such as for borrowing and returning of documents, and the ability to access documents’ information from the Web. Information retrieval technique is used in order to have an efficient access and searching process. The performance of the system is shown in term of high number of transaction, number of user and number of documents that it managed from 2001 up to 2003. This system can easily be customized so that it can be used by other small resource centers